Changes of serum midkine as a dynamic prognostic factor to monitor disease status in papillary thyroid cancer. Issue 36 (September 2018) - Li, Ning; Zhang, Chunmei; Meng, Zhaowei; Xu, Ke; He, Xianghui; Yu, Yang; Jia, Qiang; Li, Xue; Liu, Xiangxiang; Wang, Xiaoran
Abstract : Abstract: This study aimed to investigate the value of dynamic changes of midkine (MK) to monitor post-surgical patients with papillary thyroid cancer (PTC) who were managed with 131 I therapies. MK concentration at initial 131 I ablation therapy (MK1) as well as 10 to 12 months thereafter (MK2) was evaluated. And the dynamic changes of thyroglobulin (Tg) were compared (Tg1 and Tg2). Patients with MK influencing co-morbidities and with positive thyroglobulin antibodies were excluded. Concentrations of MK were measured by enzyme-linked immunosorbent assay. There were 241 PTC patients (36 males, 205 females) enrolled, 55 cases had metastases (8 males, 47 females) during their follow-up. Cox regression showed if Tg2 decreased (compared with Tg1), but not to less than 1.0ng/mL under TSH stimulation, the risk of metastases was 12.554 times more than if it could decrease to the optimal level. If Tg2 increased, the risk is 19.461 times higher. As for MK, if MK2 level decreased (compared with MK1), but not to a normal level, the risk of metastases is 3.006. If MK2 level increased, it would be 5.030 likely to had metastases. Our results indicated that MK could potentially be used as a disease monitoring biomarker for PTC, although inferior to Tg.